VD_FINDINFO HC / 2010 / 253 vom 22. Dezember 2009 - VD Tribunal cantonal (2009)
HONORAIRES, INDEMNITÉEN GÉNÉRAL, FRAIS JUDICIAIRES, DÉPENS, AVOCAT D'OFFICE, DÉFENSE D'OFFICE | 110 CPP, 27 TFJP, 28 TFJP, 30 TFJP, 9 al. 1 TFJP, 9 TFJP